Saberes alimentares tradicionais e mercados populares: uma avaliação em profundidade acerca da política municipal de fiscalização da vigilância sanitária de Fortaleza no Mercado São Sebastião - Freund, Carolina Filgueiras (2022)
This dissertation aims to evaluate the Municipal Health Surveillance Inspection Policy of Fortaleza, implemented by the Fortaleza Inspection Agency (AGEFIS). The research has as its empirical field the São Sebastião Market, which has become an expressive food distribution center, in addition to having a significant historical and cultural value for the capital of Ceará. The study analyzes the tension around that policy, data such as sanitary requirements that confront the traditional knowledge of permit holders in relation to the preparation and disposal of food products sold on the market. Therefore, the theoretical discussion takes place around cultural identities, food knowledge and evaluation of public policies. The research is based on the In-Depth Assessment approach, which basically has four major axes of analysis: policy and/or program content, contemplating its formulation, conceptual bases and internal validation; institutional institutional trajectory; temporal and territorial spectrum encompassed by the policy or program and analysis of the context of their formulation (RODRIGUES, 2008). Regarding the methodology, the nature of the study is qualitative, with analysis of official documents, bibliographical research and semi-structured interviews. We understand that the evaluation of public policy does not point to a definitive conclusion, or to a solution, but to the understanding of the subjectivities around it. In this way, the exposition of the data collected during the research allowed us to conclude that it is not enough for inspection to be concerned with complying with the provisions set forth in the legislation, it is necessary that the management and cultural issue of public markets are able to be fulfilled so that the population benefits from two aspects, sanitary hygiene and culture.